2014
DOI: 10.1083/jcb.201404025
|View full text |Cite
|
Sign up to set email alerts
|

A single domain of the ZP2 zona pellucida protein mediates gamete recognition in mice and humans

Abstract: The ZP251–149 domain is necessary for human and mouse gamete recognition on the surface of the zona pellucida and for mouse fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(182 citation statements)
references
References 43 publications
8
169
0
Order By: Relevance
“…Initially, ZP2, a major component of the ZP matrix, was proposed to serve as a ligand for secondary sperm binding (for acrosome-reacted spermatozoa) to the surface of the ZP. Recent work using mouse oocytes expressing "humanized" zona proteins by replacing mouse ZP1-3 with human ZP1-4 clearly showed that ZP2 but not ZP3 is necessary and sufficient for binding and penetration of human spermatozoa to the humanized ZP matrix (Avella et al 2014). Thus, the same pair of molecules might keep working through the entire process, from initial contact until final penetration of the ZP.…”
Section: Penetration Of the Zpmentioning
confidence: 97%
See 1 more Smart Citation
“…Initially, ZP2, a major component of the ZP matrix, was proposed to serve as a ligand for secondary sperm binding (for acrosome-reacted spermatozoa) to the surface of the ZP. Recent work using mouse oocytes expressing "humanized" zona proteins by replacing mouse ZP1-3 with human ZP1-4 clearly showed that ZP2 but not ZP3 is necessary and sufficient for binding and penetration of human spermatozoa to the humanized ZP matrix (Avella et al 2014). Thus, the same pair of molecules might keep working through the entire process, from initial contact until final penetration of the ZP.…”
Section: Penetration Of the Zpmentioning
confidence: 97%
“…Nonetheless, IVF is still a promising approach for discovering new molecular models for sperm-ZP interactions (Visconti and Florman 2010;Redgrove et al 2012;Nagdas et al 2015). A recent study using gene rescue experiments clearly demonstrated that human spermatozoa could recognize the human zona pellucida protein ZP2 (Avella et al 2014). The N-terminal domains (spanning amino acid residues 39-154 or 39-267) of human ZP2 exhibited high affinity for spermatozoa and enabled sperm binding to the ZP matrix.…”
Section: Adhesion To the Zpmentioning
confidence: 98%
“…We cloned rat IE3, a monoclonal antibody that binds the amino terminus of mouse ZP2, a critical ligand for taxon-specifi c sperm binding [8] ( Figure S2A). IE3 transiently inhibits female mouse fertility when introduced as ascites fl uid through intraperitoneal injection [9].…”
Section: Magazinementioning
confidence: 99%
“…The HISRainbow construct was generated by sequentially ligating lox 2272+lox N+lox P, polyA×3+lox 2272, H3.3-eGFP, polyA+lox N, H3.3 R26K -eCFP, polyA+lox P, H3.3 K27R -mCherry, polyA+frt (all with 5′ XbaI restriction sites and 3′ NheI or EcoRI restriction sites) into the pCAGEN plasmid (Addgene) (Rinkevich et al, 2011). After digestion with SpeI and EcoRI, the transgene was gelpurified and injected into the male pronucleus (Avella et al, 2014). These mice were then crossed with Flpe-Cre transgenic mice (Jackson Laboratory) for several generations until only one copy of transgene was detected in the mouse line.…”
Section: Micementioning
confidence: 99%